Kogălniceanu în corespondenţă (III) Scrisori din timpul studiilor la Lunéville şi Berlin (1834–1838) - Andrei Nestorescu (Revista de Istorie și Teorie Literară)
Andrei Nestorescu publishes some letters Mihail Kogălniceanu addresses to his father and sisters, but especially to his father. The letters he writes to his sisters are all in French. He shares with them his experience as a student in Lunéville and Berlin, between 1834 and 1838, and he thanks them for the concern and the care they show for his well-being. Besides the letters, Andrei Nestorescu publishes as well a list containing the names Kogălniceanu refers to and an explanatory dictionary for all the words used by Kogălniceanu (regionalisms and archaisms).